Readiness Analysis of Structure Smart City in Wonogiri Regency (Future Science, 2021)
Digital transformation is happening at a rapid pace. Local governments are forced to adapt to the fast-changing technology. however, not all local governments are able to adapt to the changing digital environment. then there needs to be preparation for the implementation of digital-based local governance or often called a smart city.This paper focuses on analyzing the readiness of Wonogiri Regency in implementing a smart city, especially structural readiness. Researchers collected data by interviewing informants and secondary data. The results of the study show based on the structure, Wonogiri Regency is quite ready to organize a smart city.